Chemotherapy naive breast cancer: a correlation study between BD Cytorich™ Red cell blocks and formalin- fixed paraffinembedded tissue blocks - Van Rooyen, Evelyn (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.